The success of Cafe Biji Kopi: digital marketing, café atmosphere, and Gen-Z lifestyle - Pane, Dewi Nurmasari; Sentosa, Ilham; Sharin, Farah Hida (Indonesia Research and Study Center, 2025)
This study aims to analyze the influence of digital marketing, Gen Z lifestyle, and Cafe atmosphere on purchasing decisions at Cafe Biji Kopi. The research employs a quantitative approach using a survey method, with a questionnaire that was tested for validity during a pilot study involving 30 respondents and subsequently deemed valid. The research sample consists of 96 respondents who are Gen Z consumers of Cafe Biji Kopi. Data were analyzed using a multiple linear regression model with the assistance of SPSS version 27 software. The main findings indicate that digital marketing, lifestyle, and Cafe atmosphere have a positive and significant effect on purchasing decisions, both partially and simultaneously. The implications of this study emphasize that the success of modern Cafes is not solely determined by product quality, but also by the effective implementation of digital marketing strategies, alignment with the lifestyle of Gen Z, and the creation of a Cafe atmosphere that provides a positive consumer experience. Therefore, the results of this study are expected to serve as a practical reference for Cafe managers in formulating marketing strategies that are adaptive to the characteristics of Gen Z.